Analysis Of Dribbling Skills Of Extracurricular Soccer Participants In Senior High School Students 17 Gowa - Muhammad Qasash Hasyim; Andi Ridwan; Ishak Bachtiar; Muh. Ikbal Amal (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
This research is a type of descriptive research that uses a